2019
DOI: 10.1093/nar/gkz1147
|View full text |Cite
|
Sign up to set email alerts
|

The human methyltransferase ZCCHC4 catalyses N6-methyladenosine modification of 28S ribosomal RNA

Abstract: RNA methylations are essential both for RNA structure and function, and are introduced by a number of distinct methyltransferases (MTases). In recent years, N6-methyladenosine (m6A) modification of eukaryotic mRNA has been subject to intense studies, and it has been demonstrated that m6A is a reversible modification that regulates several aspects of mRNA function. However, m6A is also found in other RNAs, such as mammalian 18S and 28S ribosomal RNAs (rRNAs), but the responsible MTases have remained elusive. 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 80 publications
3
89
0
Order By: Relevance
“…Consistent with this finding, van Tran et al confirmed ZCCHC4 as a 28S rRNA m 6 A4220 methyltransferase that acts only on rRNAs [82], and further studies on the structure and regulation of ZCCHC4 in m 6 A methylation of 28S rRNA showed that the specific binding and methylation of ZCCHC4 to substrates depended on the stem loop structure of 28S rRNA [83]. In addition, the findings that ZCCHC4 is located in nucleoli, where the ribosomes are assembled, and ZCCHC4 interacts with proteins involved in RNA metabolism provide a possible mechanism by which ZCCHC4 influences RNA translation by regulating ribosomal assembly and biogenesis [84].…”
Section: Ribosomal Rnasmentioning
confidence: 97%
“…Consistent with this finding, van Tran et al confirmed ZCCHC4 as a 28S rRNA m 6 A4220 methyltransferase that acts only on rRNAs [82], and further studies on the structure and regulation of ZCCHC4 in m 6 A methylation of 28S rRNA showed that the specific binding and methylation of ZCCHC4 to substrates depended on the stem loop structure of 28S rRNA [83]. In addition, the findings that ZCCHC4 is located in nucleoli, where the ribosomes are assembled, and ZCCHC4 interacts with proteins involved in RNA metabolism provide a possible mechanism by which ZCCHC4 influences RNA translation by regulating ribosomal assembly and biogenesis [84].…”
Section: Ribosomal Rnasmentioning
confidence: 97%
“…In addition to the MTC, other m 6 A writers have also been identified in recent years, including METTL16, METTL5, and ZCCHC4 ( Fig. 1a and Table 1), which are responsible for the deposition of m 6 A into structured RNAs, such as U6 snRNA, 28S rRNA, and 18S rRNA, and in some cases, the introns of mRNA [15][16][17][18][19][20][21][22]. The MTC core component METTL3-METTL14 heterodimer catalyzes most of m 6 A methylations in mRNA, with METTL3 being the only catalytic subunit that uses Sadenosylmethionine (SAM) as the methyl donor [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…ZCCHC4 has a potential m6A methyltransferase domain, with conserved catalytic motif “DPPF” and CCHC-ZNF domain, and can induce m6A methylation at 4220 in human 28srRNA ( 52 , 53 ). When deleted, the accumulated level of m6A is significantly reduced in total rRNA, leading to unsteadiness in ribosome activity, which is associated with codon specific translation defects ( 54 ).…”
Section: Structure and Function Of M6a Enzyme Systemmentioning
confidence: 99%